Nonionic/Anionic Mixed Surfactants System for Colorimetric Determination of Metal-Dithizone Complexes. - ABU-SHAMMALA., FARID (Asian Journal of Chemistry, 2010)
Dithizone (diphenyl thiocarbazone, H2Dz) has been solubilized in a mixed micellar solution of nonionic (poly (oxyethylene) (23) dodecanol) (Brij 35) and anionic (sodium dodecylsulfate) (SDS) surfactants. Increasing the surfactants concentration above the critical micelle concentration produces more micelles that provide local nonpolar microenvironments that enhance the solubility of the nonpolar organic compounds in water. Metal ions bind the mixed micellar-solubilized dithizone to form water-soluble colored chelates. Tile metal-dithizone colored complexes are extracted to the nonpolar "stationary" micellar phase. Potential application of the method for the determination of different metal ions in water has been evaluated. The detection limit of the method ranged from 3 to 6 ppb. Recoveries from individual metal ion solution ranged from 95 to 100% with RSDs between 4-10%, and from mixed metal ions solution ranged from 93-104% with RSDs between 3.5-12%. The recoveries of metal ions obtained in our method are better than the recoveries obtained with the use of extraction in toxic chlorinated hydrocarbons method.